2016
DOI: 10.1038/srep35942
|View full text |Cite
|
Sign up to set email alerts
|

New generation ICG-based contrast agents for ultrasound-switchable fluorescence imaging

Abstract: Recently, we developed a new technology, ultrasound-switchable fluorescence (USF), for high-resolution imaging in centimeter-deep tissues via fluorescence contrast. The success of USF imaging highly relies on excellent contrast agents. ICG-encapsulated poly(N-isopropylacrylamide) nanoparticles (ICG-NPs) are one of the families of the most successful near-infrared (NIR) USF contrast agents. However, the first-generation ICG-NPs have a short shelf life (<1 month). This work significantly increases the shelf life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…This scenario usually happens when the imaging target is located at a small depth (≈1–2 cm). The setting in our previous studies using the PNIPAM nanoparticles fits in this situation . However, when the imaging target is deep (>2 cm), the fluorescence generated from the (non‐100%‐off) USF contrast agents may be significantly attenuated due to tissue's scattering.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This scenario usually happens when the imaging target is located at a small depth (≈1–2 cm). The setting in our previous studies using the PNIPAM nanoparticles fits in this situation . However, when the imaging target is deep (>2 cm), the fluorescence generated from the (non‐100%‐off) USF contrast agents may be significantly attenuated due to tissue's scattering.…”
Section: Discussionmentioning
confidence: 93%
“…To study the fluorescence intensity changes in response to the temperature changes, an in‐house built system was implemented . Briefly, a 3 mL sample was transferred into a quartz cuvette (Hellma, Germany) and then immersed in a water bath.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6] We recently developed a new imaging method for deep-tissue high-resolution imaging, which has been termed as ultrasound-switchable fluorescence (USF). [7][8][9][10][11][12][13] It has been demonstrated that USF can simultaneously achieve high SNR (or sensitivity) and high spatial resolution in tissue with a depth of centimeters. [7][8][9][10][11][12][13] In this study, we report a new method to further improve the SNR (or sensitivity) of the USF imaging without sacrificing the spatial resolution by modulating the ultrasound exposure.…”
Section: Introductionmentioning
confidence: 99%